(3cJGH GdbQBFI gh eYde GdYdhe hGdafhfs - (3eMeO Hf Ydj GdRTcjs ((3eMeO Hf CHj GdaVd GdUGFZi s)
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdRTci QMeg Gddg bQCJ GdbQCf ef Chdg Edi BNQI HQhGjI CHj YeQ GdOhQi Ydi GdTjN GdLdjd GdSjO LOi CHj GdYHGS eMeO Hf CHj GdbSe GdHGQi s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg (B: (3ShQI bQjT hQhi Yfg Cfg jfRd GdJSejI ai Chd ShQI bQjT ShQI GdcGaQjf (B((3hdi Ojf(B) (3SGcfI GdjGA ShQI JHJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(1511) s
Keywords: (3GdbQGAGJ hGdJLhjOs